Gut REG3γ-Associated Lactobacillus Induces Anti-inflammatory Macrophages to Maintain Adipose Tissue Homeostasis - Huang, Yugang; Qi, HouBao; Zhang, Zhiqian; Wang, Enlin; Yun, Huan; Yan, Hui; Su, Xiaomin; Liu, Yingquan; Tang, Zenzen; Gao, Yunhuan; Shang, Wencong; Zhou, Jiang; et al. (Frontiers in Immunology, 2017)
Gut microbiota may not only affect composition of local immune cells but also systemic immune cells. However, it is not completely clear how gut microbiota modulate these immune systems. We here found that there have expanded macrophage pools in huREG3γ tgIEC mice. REG3γ associated Lactobacillus, which is homology to Lactobacillus Taiwanese, could enlarge macrophage pools not only in the small intestinal lamina propria but also in the spleen and adipose tissues. STAT3 mediated signal(s) was a critical factor in the Lactobacillus mediated anti-inflammatory macrophages. We also offered evidence for critical cellular links among REG3γ associated Lactobacillus, tissue macrophages and obesity diseases. Anti-inflammatory macrophages in the lamina propria which are induced by REG3γ-associated Lactobacillus, may migrate into adipose tissues and are involved in resistance against high-fat diet mediated obesity. Thus, REG3γ-associated Lactobacillus induced anti-inflammatory macrophages in gut tissues may play a role in adipose tissue homeostasis.